Proposal of an additional-inertia tuning method to viscous load for high speed motion training - Shigetoshi, K.; Kawamura, S.; Isaka, T. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
This research proposes a new training system for high speed motions. In the proposed training system, a relatively small inertia is added to a viscous load in order to increase the load without decreasing the maximum speed. Moreover, in order to increase energy consumption of humans, we artificially make the additional inertia zero during motions. Consequently, the additional inertia is tuned to increase the load torque and the energy with keeping the maximum speed. The effectiveness of the proposed system is verified by some experimental results.